Examination Of Sport Managers' Self-Efficacy Status And Time Management - Ali Erdoğan; Erkan Faruk Şirin; Pınar Karacan Doğan; Ahmet Azmi Yetim (Türk Spor ve Egzersiz Dergisi)
The aim of this study is to determine the self-efficacy perceptions and time management belief levels of the public and sports club managers working in Turkey and to examine the relationship between them by examining them according to some demographic variables. In this research, a method for descriptive and relational screening was used to reveal the current situation. The sample group of the public and sports club managers working in Turkey consists of public sports managers (n = 55) and sports club managers (n = 99) who volunteered to participate in the study. Personal Information Form, Sport Managers Self-Efficacy Scale and Time Management Scale were used as data collection tools. In the analysis of data, since the data and groups are not distributed homogeneously and the data is skewed to the left, non-parametric Mann Whitney U and Kruskal Wallis test techniques were used to determine the differences between the groups in the sub-dimensions of self-efficacy and time management, and Spearman Correlation Analysis technique was used in the relationship between Sport Managers' Self-Efficacy Scale and Time Management Scale. At the end of the study, there were no significant differences between Sport Managers Self-Efficacy and Time Management beliefs and Personal variables (age, gender, marital status, education level, year of service, management year and sports history), while a significant difference was determined between the time attitude sub-dimension of time management and the sector variable in favor of sports club managers. In addition, a weak positive and significant (p lt;0.05) relationship was found between general time management and sports managers' self-efficacy (decision-making, personal characteristics, Knowledge and Interpersonal Roles).